2018
DOI: 10.1016/j.ijleo.2018.08.134
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on morphology, growth mode and indium incorporation in MOCVD grown InGaN/n-GaN heterostructures

Abstract: InGaN layers were grown on n-GaN/GaN/sapphire template using metal organic chemical vapor deposition system by varying Indium (In) flow rate as 11, 13 and 14 µmol/min. The nanoisland growth mode was observed by atomic force microscopy. The thickness and composition of In in the InGaN layers were determined by high resolution X-ray diffraction technique. The composition of In was found to be 15-17% depending on the In flow rate. Photoluminescence from the InGaN layers exhibit multiple peaks ranging between 479 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…1, a small bump beside the InGaN peaks for all samples can be observed. This indicates a slight indium composition fluctuation due to the inhomogeneous indium distribution across the thin film [16]. The indium composition fluctuations are estimated to vary around ± 1-6% for all samples.…”
Section: Resultsmentioning
confidence: 85%
“…1, a small bump beside the InGaN peaks for all samples can be observed. This indicates a slight indium composition fluctuation due to the inhomogeneous indium distribution across the thin film [16]. The indium composition fluctuations are estimated to vary around ± 1-6% for all samples.…”
Section: Resultsmentioning
confidence: 85%
“…The superoxide radicals thus formed react with the holes and photogenerated electrons, forming hydroxyl radical species (OH • ) (steps 3 and 4). The active species (O 2 •– and OH • ) formed play a key role in degrading the organic pollutants (steps 5 and 6). , …”
Section: Resultsmentioning
confidence: 99%
“…•− and OH • ) formed play a key role in degrading the organic pollutants (steps 5 and 6). 14,49 The steps involved in degradation reaction pathways are as follows. It can be concluded that due to the effect of the wide band gap of TiO 2 NRs (3.04 eV), the probability of electron−hole pair generation or annihilation will be very less.…”
Section: High-resolution Transmission Electron Microscope (Hrtem) Ana...mentioning
confidence: 99%
“…This is mainly attributed to its tunable direct bandgap energy characteristics from 0.70 eV (infrared) to 3.42 eV (ultraviolet) by varying the indium (In) composition. Thus, InGaN is an excellent candidate for solar cell application since it can cover almost the entire spectrum from solar irradiation [5]. The incorporation of indium nitride (InN) improved the radiation resistance of InGaN when subjected to proton irradiation, which dominates the radiation environment in space.…”
Section: Introductionmentioning
confidence: 99%